ORGANIC REVELATION IN THE THEOLOGY OF HERMAN BAVINCK - Phen, Rudy (STT Reformed Injili Internasional, 2018)
The reality of the Trinity compels Bavinck to view the revelation as one single historical and organic whole, a mighty world controlling and world-renewing system of testimonies and acts of God. Organism is the appropriate apparatus to describe the unity-in-diversity of the external (ad extra) work of the triune God and it serves as an agent of unity in Bavinck's theology. He has formulated a unified and organic Reformed doctrine of revelation that is founded on his Trinitarian vision and has presented it as the key concept of Christian worldview.KEYWORDS: Trinity; Herman Bavinck; revelation; organic; unity-indiversity; worldview; ad intra; ad extra.